SEG Technical Program Expanded Abstracts 2020 2020
DOI: 10.1190/segam2020-3427522.1
|View full text |Cite
|
Sign up to set email alerts
|

Extrapolating low-frequency prestack land data with deep learning

Abstract: Missing low-frequency content in seismic data is a common challenge for seismic inversion. Long wavelengths are necessary to reveal large structures in the subsurface and to build an acceptable starting point for later iterations of full-waveform inversion (FWI). High-frequency land seismic data are particularly challenging due to the elastic nature of the Earth contrasting with acoustic air at the typically rugged free surface, which makes the use of low frequencies even more vital to the inversion. We propos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…The approach is suitable for elastic waveform inversion in marine survey layout. Fang et al [42] and Ovcharenko et al [43] extrapolated low frequencies by training convolutional networks on AGC-balanced patches of time-domain seismic data in marine and land setups, respectively. Aharchaou and Baumstein [44] avoided using synthetic data and trained a UNet neural network to translate knowledge of low-frequency data from OBN surveys to band-limited shallow streamer data.…”
Section: B Reconstruction Of Missing Low-frequency Datamentioning
confidence: 99%
“…The approach is suitable for elastic waveform inversion in marine survey layout. Fang et al [42] and Ovcharenko et al [43] extrapolated low frequencies by training convolutional networks on AGC-balanced patches of time-domain seismic data in marine and land setups, respectively. Aharchaou and Baumstein [44] avoided using synthetic data and trained a UNet neural network to translate knowledge of low-frequency data from OBN surveys to band-limited shallow streamer data.…”
Section: B Reconstruction Of Missing Low-frequency Datamentioning
confidence: 99%
“…To mitigate potential bias toward the more energetic aspects of seismic records, amplitude balancing techniques are introduced, including automatic gain control [21]. Further, a frequency band expansion method rooted in the time-space domain was explored [22], with an emphasis on utilizing low-frequency remote offset seismic records for training neural networks and predicting the low-frequency components. However, this approach can amplify both weak energy seismic signals and noise, adversely affecting prediction outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Aharchaou et al (2020) showed a field data application on ocean-bottom node data. Elastic land data was extrapolated in synthetic setup in (Ovcharenko et al, 2020;Sun and Demanet, 2020). Low-wavenumber velocity model was recovered from early FWI gradients and directly from the data in Plotnitskii et al (2020) and Kazei et al (2019b), respectively.…”
mentioning
confidence: 99%